A REVIEW ON OSMOTICALLY CONTROLLED DRUG DELIVERY SYSTEMS - Sharma, Amit; Kumar, Damit; Painuly, Neelam (Asian Journal of Pharmaceutical Research and Development, 2018)
Osmotically controlling drug delivery system is one of the best method of drug technology it is highly fruitful and effective. In this osmotic pressure is used to deliver drug properly as osmosis is the movement from lower concentration to the higher concentration. By this system we can release drug in proper manner as it is widely accepted technique with interesting facts and use. There are various drug delivery components like drugs. Osmotic agent and semi permeable membrane all are essential and have their own role to play, It is one of the best in best method used now a days to get best results.